(untitled) (Research, Society and Development, 2020)
This research aims to compare Odebrecht’s results, through the financial statements, after the Lava Jato operation. Therefore, a survey was made about which companies were involved in the operation. The research is characterized as bibliographic, since it was carried out based on records available from the company itself. Regarding the approach to the problem, the research is quantitative, as it analyzes the annual reports released by the organization in the years 2013, 2014 and 2015. As a result of the analyzes made through the financial statements, it can be seen that the company Odebrecht does not have good results. results, through analysis of the financial statements, after the launch of the Lava Jato operation. To this end, it is suggested for future research work on the Lava Jato operation, that seek to analyze the companies involved in this operation that are based in Southeast Brazil, and compare their development before and after the scandal triggered by the Federal Police, to be more in-depth and observed variables that were not analyzed in the present study.